A NARRATIVE STUDY OF INDONESIAN PRE-SERVICE TEACHERS’ EXPERIENCES IN TEACHING INTERNSHIP IN THAILAND - amanda shofia; Fitri Budi Suryani; Rismiyanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines how pre-service Indonesian English teachers adapt their teaching strategies and develop their professional identities when facing cross-cultural challenges in the classroom during their teaching practicum in Thailand. A qualitative design using a narrative inquiry approach was employed to gain a comprehensive understanding of the participants’ personal narratives and reflections. Two pre-service teachers from the English Education Department of a private university in Central Java, Indonesia, participated after completing a one-month teaching internship at the Institute of Al-Abdia and Santi Witya Serong in Thailand. Data were collected through in-depth interviews and reflective journals, then analyzed using thematic analysis. Three main themes emerged: challenges in teaching strategies, professional identity development, and cross-cultural teaching experiences. Regarding challenges in teaching strategies, participants faced significant language barriers and limited learning resources, which encouraged them to use code-switching and develop self-made learning materials. In terms of professional identity development, participants demonstrated growth through self-preparation, adaptation, emotional regulation, and increased self-confidence. In terms of cross-cultural teaching experience, participants must navigate diverse classroom dynamics and student diversity, which require the application of culturally responsive teaching approaches. Overall, the international teaching internship program in Thailand provides a meaningful and transformative experience that significantly contributes to participants’ long-term professional growth. These findings highlight the importance of institutional support in preparing prospective teachers to navigate cross-cultural teaching contexts.